USE OF STEROIDS IN RHINOPLASTY WITH LATERAL OSTEOTOMIES FOR REDUCING POST OPERATIVE OEDEMA - Sanober, Aamna; Rashid, Mamoon; Ibrahim Khan, Mohammad; Sarwar, Saad Ur Rehman; Yousaf, Shumaila; Orakzai, Ishtiaq Ur Rehman; Fatima, Samia; Eitezaz, Farhan Ahmed; Khan, Adeela Hussain (Journal of Ayub Medical College Abbottabad, 2018)
Background Postoperative periorbital edema is a commonly encountered side effect of rhinoplasties in which lateral osteotomies have been incorporated. It dissatisfies the surgeon as well as the patient. Osteotomies are done at the end of all soft tissue manipulation to reduce the development of edema. The aim of this study was to determine the efficacy of intravenous dexamethasone in reducing edema in patients who undergo rhinoplasty with lateral osteotomies. Methods A Prospective randomized controlled trial was done at department of plastic and reconstructive surgery, Shifa International Hospital Islamabad. Sixty patients age between 16- 55 requiring open rhinoplasty were taken for this study and divided in two groups. One group received dexamethasone 8mg intravenously peroperatively and second dose 4 hours postoperatively. The second group did not receive anything. Both groups were assessed on first post operative day and 7th day for periorbital edema. Result The overall decrease in edema in patients who received steroid was by 50% while in control group was 33.3%. By the 7th day control group 13.3% patients had grade III edema as compared to 3.33% in steroid group. Chi test was applied and p value of 0.0289 was obtained which was found to be statistically very significant. Conclusion Dexamethasone used in minimal dosage showed significant advantage in reducing periorbital edema after rhinoplasty with no evidence of any side effects secondary to steroid administration. Keywords: Rhinoplasty, Lateral osteotomy, Steroid use in rhinoplasty Background: Postoperative periorbital oedema is a commonly encountered side effect of rhinoplasties in which lateral osteotomies have been incorporated. It dissatisfies the surgeon as well as the patient. Osteotomies are done at the end of all soft tissue manipulation to reduce the development of oedema. The aim of this study was to determine the efficacy of intravenous dexamethasone in reducing oedema in patients who undergo rhinoplasty with lateral osteotomies. Methods: A Prospective randomized controlled trial was done at department of plastic and reconstructive surgery, Shifa International Hospital Islamabad. Sixty patients age between 16-55 requiring open rhinoplasty were taken for this study and divided in two groups. One group received dexamethasone 8mg intravenously preoperatively and second dose 4 hours postoperatively. The second group did not receive anything. Both groups were assessed on first post-operative day and 7th day for periorbital oedema. Result: The overall decrease in oedema in patients who received steroid was by 50% while in control group was 33.3%. By the 7th day control group 13.3% patients had grade III oedema as compared to 3.33% in steroid group. Chi test was applied and p-value of 0.0289 was obtained which was found to be statistically very significant. Conclusion: Dexamethasone used in minimal dosage showed significant advantage in reducing periorbital oedema after rhinoplasty with no evidence of any side effects secondary to steroid administration. Keywords: Rhinoplasty; Lateral osteotomy; Steroid